TINJAUAN HUKUM ISLAM TERHADAP PRAKTIK DROPSHIPPING DALAM E-COMMERCE INDONESIA - Gyas Khairan; Jazlynne Attia Pradnya Ubaedi; Muhammad Mirza Ar Rabbani (Media Riset Bisnis Manajemen Akuntansi, 2025)
The digital trade sector has grown rapidly as a result of advancements in IT, including the e-commerce drop-shipping approach. Drop-shipping is a business practice in which a company sells products without keeping stock; instead, they order the product from a third party after receiving a customer order. This study analyzes Islamic law for dropshipping e- commerce in Indonesia, although this method is becoming increasingly popular due to its ease and success. There are many questions about its legitimacy according to Islamic law, especially concerning the principles of honesty, ownership of goods, and the prohibition of gharar. A normative approach was used to conduct this study. It included qualitative analysis of literature related to fiqh muamalah, fatwas of scholars, and regulations.Keywords : Dropshipping, E-commerce, Fiqh Muamalah, Gharar, Islamic Law